Improving the activity of Trichoderma reesei cel7B through stabilizing the transition state. Issue 6 (17th December 2015) - Wang, Yefei; Song, Xiangfei; Zhang, Shujun; Li, Jingwen; Shu, Zhiyu; He, Chunyan; Huang, Qingshan; Yao, Lishan
ABSTRACT: Trichoderma reesei ( Tr .) cellulases, which convert cellulose to reducing sugars, are a promising catalyst used in the lignocellulosic biofuel production. Improving Tr . cellulases activity, though very difficult, is highly desired due to the recalcitrance of lignocellulose. Meanwhile, it is preferable to enhance the cellulase's promiscuity so that substrates other than cellulose can also be hydrolyzed. In this work, an attempt is made to improve the catalytic activity of a major endogluanase Tr . Cel7B against xylan which crosslinks with cellulose in lignocellulose. By using quantum mechanics/molecular mechanics (QM/MM) molecular dynamics (MD) simulations, the transition state of the xylo‐oligosaccharide hydrolysis is identified. Then, mutations are introduced and their effect on the transition state stabilization is ranked based on the free energy calculations. Seven top ranked mutants are evaluated experimentally. Three mutants A208Q, A222D, and G230R show a higher activity than the wild‐type Tr . Cel7B in the hydrolysis of xylan (by up to 47%) as well as filter paper (by up to 50%). The combination of the single mutants can further improve the enzyme activity. Our work demonstrates that the free energy method is effective in engineering the Tr . Cel7B activity against xylan and cellulose, and thus may also be useful for improving the activity of other Tr . cellulases. Biotechnol. Bioeng. 2016;113: 1171–1177. © 2015 Wiley Periodicals, Inc. Abstract : The authors improved the activity of Tr . Cel7B using a computer aided protein rational design method. The mutants displayed higher activity against cellulose and xylose.